2020
DOI: 10.1021/acsnano.9b08737
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Nitride Hollow Theranostic Nanoregulators Executing Laser-Activatable Water Splitting for Enhanced Ultrasound/Fluorescence Imaging and Cooperative Phototherapy

Abstract: The limited efficacy of “smart” nanotheranostic agents in eradicating tumors calls for the development of highly desirable nanoagents with diagnostics and therapeutics. Herein, to surmount these challenges, we constructed an intelligent nanoregulator by coating a mesoporous carbon nitride (C3N4) layer on a core–shell nitrogen-doped graphene quantum dot (N-GQD)@hollow mesoporous silica nanosphere (HMSN) and decorated it with a P-PEG-RGD polymer, to achieve active-targeting delivery (designated as R-NCNP). Upon … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
109
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(109 citation statements)
references
References 67 publications
0
109
0
Order By: Relevance
“…The laser power density of 1.0 W cm −2 was employed in this work, which is considered as safe and acceptable in the previously reported work for in vivo photothermal evaluation. [ 21,49,50 ]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The laser power density of 1.0 W cm −2 was employed in this work, which is considered as safe and acceptable in the previously reported work for in vivo photothermal evaluation. [ 21,49,50 ]…”
Section: Resultsmentioning
confidence: 99%
“…The laser power density of 1.0 W cm −2 was employed in this work, which is considered as safe and acceptable in the previously reported work for in vivo photothermal evaluation. [21,49,50] Excitingly, the RPA assemblies underwent secondary selfassembly under NIR laser irradiation. The PLGA segments of monodispersed RPA were fused together into larger hierarchal superstructure with two or more rings on the surface of PLGA matrix (Figure 6h and Figure S11, Supporting Information).…”
Section: Photothermal Property and Photoacoustic Imaging Of Rpamentioning
confidence: 99%
“…The injection concentration was determined based on in vitro experiments, which is consistent with previous studies. [ 28 ] As shown in Figure 5b, the CSNPs@Cu‐BIF nanoassemblies were injected intravenously into nude mice for 12 h (the maximum accumulation time of the sample in the tumor), and thermal imaging was recorded under 808 nm laser irradiation. In G4, the temperature of the tumor increases to 57.5 °C in 7 min, which is sufficient to effectively eliminate solid tumors.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, we found that manganese dioxide nanoparticles (MnO 2 ) were a safe and effective nano-agent that could improve a hypoxic and acidic tumor microenvironment 13 - 15 . MnO 2 efficiently reacted to the excessive H 2 O 2 and H + in the TME and generated oxygen to modulate hypoxic, acidic, and high-ROS tumor microenvironments 16 - 20 . Therefore, we wanted to explore the possibility of MnO 2 as an autophagy inhibition.…”
Section: Introductionmentioning
confidence: 99%